Imaging voltage in zebrafish as a route to characterizing a vertebrate functional connectome: promises and pitfalls of genetically encoded indicators. (2nd April 2016) - Kibat, Caroline; Krishnan, Seetha; Ramaswamy, Mahathi; Baker, Bradley J.; Jesuthasan, Suresh
Abstract: Neural circuits are non-linear dynamical systems that transform information based on the pattern of input, current state and functional connectivity. To understand how a given stimulus is processed, one would ideally record neural activity across the entire brain of a behaving animal, at cellular or even subcellular resolution, in addition to characterizing anatomical connectivity. Given their transparency and relatively small size, larval zebrafish provide a powerful system for brain-wide monitoring of neural activity. Genetically encoded calcium indicators have been used for this purpose, but cannot directly report hyperpolarization or sub-threshold activity. Voltage indicators, in contrast, have this capability. Here, we test whether two different genetically encoded voltage reporters, ASAP1 and Bongwoori, can be expressed and report activity in the zebrafish brain, using widefield, two-photon and light sheet microscopy. We were unable to express ASAP1 in neurons. Bongwoori, in contrast expressed well, and because of its membrane localization, allowed visualization of axon trajectories in 3D. Bongwoori displayed stimulus-evoked changes in fluorescence, which could be detected in single trials. However, under high laser illumination, puncta on neural membranes underwent spontaneous fluctuations in intensity, suggesting that the probe is susceptible to blinking artefacts. These data indicate that larval zebrafish can be used to image electrical activity in the brain of an intact vertebrate at high resolution, although care is needed in imaging and analysis. Recording activity across the whole brain will benefit from further developments in imaging hardware and indicators.